Morphological and Biochemical Characterization of Different Oyster Mushroom (Pleurotus spp.) - A. K. Jaitly, Shubhra Shukla* and (Journal of Phytology, 2011)
Mushrooms have medicinal as well as nutritive value and extensively used as human food from the time immortal. In order to determine the genetic diversity among Pleurotus species of mushroom using morphological and random amplified polymorphic DNA (RAPD) markers, about seven different species were collected. Out of the seven, five species, naming Pleurotus citriopileatus, Pleurotus djamor, Pleurotus Florida, H. ulmarius and Pleurotus sajor-caju were selected. Five different morphological traits i.e., mycelial growth (mm), stipe length(cm), cap diameter (cm), margin of fruit body, colour of fruit body, total yield (kg), carbohydrate content(%) and protein content (%) were recorded. Results indicate that all the five species of Pleurotus shows great diversity in their morphological characters and biochemical parameters. Thus all these species have a great genetic diversity.